Estudo da fauna flebotomínica e dos aspectos ambientais relacionados à transmissão das leishmanioses no município de Juatuba, MG ,Brasil - 2015 à 2016 - Laiza Bonela Gomes (2017)
The study was conducted in Juatuba, Minas Gerais, whose previous data from human and canine leishmaniasis point to a complex profile of this disease in the municipality.The main objective was to study the phlebotominae fauna, the epidemiological, climatic and environmental aspects related to the transmission of leishmaniasis, in the city and to correlate the study variables with the prevalence of canine visceral leishmaniasis (CVL). A prospective epidemiological study of systematic sampling of phlebotomine and canine serological survey was carried out from April 2015 to March 2016. The entomological study was carried out in two study areas,namely: Area 1 - Satelite I and II; Area 2 - Vila Maria Regina (VMR) contemplated the neighborhoods VMR I and II. Twenty-four light traps were installed in 12 residences distributed in the two study areas. At each capture point, two traps were installed, located in the intradomicile and peridomicile. The collections were done systematically, in the last week of each month, for 12 months. For the analysis of the climatic aspects, we used the simple Spearman correlation for each pair of variables and for spatial analysis we used Kernel estimation, K function and Fuzzy logic. To determine the prevalence rate of CVL, blood samples were collected from dogs distributed in two study areas, to perform the TR-DPP screening test and the ELISA confirmatory serological diagnostic test. In relation to the entomological study, 431 sandflies were captured, being 69% male and 74% of the total coming from the peridomicile. The species Lutzomyia Longipalpis was captured in greater numbers (44%). Regarding the natural infection, of the 89 females submitted to PCR analysis, 5.5% presented positivity to the infection by Leishmania sp. Of those, 100% of the females were infected with Leishmania infantum and belonged to the VMR. Regarding climatic factors, the mean temperature variable presented a positive correlation (p <0.05) with the monthly vector density variation and the relative humidity presented negative correlation (p <0.05). The monthly precipitation variable presented a negative correlation in relation to the monthly vector density, with no statistical significance. The canine survey was performed in 1.752 dogs, 1163 were from Satelite and 589 from VMR, with a prevalence rate of 4.12% and 7.13%, respectively, being this significant difference between the areas. The two areas of the municipality presented favorable environmental conditions for the maintenance of leishmaniasis, especially CVL, with Lu. longipalpis, presence of canine infection and Le. infantum detection in vectors, indicating that the parasite-reservoir-vector interface is active in the studied areas. Surveillance and control actions should be directed mainly to the VMR, since it presented vectorial breeding sites and the analyzes indicated to be an area more favorable to the affection of visceral leishmaniasis, due to greater vector density, greater canine positivity, presence of vector Le. infantum and environmental conditions with high presence of risk factors.